Socioeconomic, financial and production infrastructure profile of farmers in rural settlements in the western region of the state of São Paulo, Brazil - Maziero, Luana Possari; Oliveira, Sandra Cristina [UNESP]; Pinto, Leonardo de Barros [UNESP]; Higuchi, Mauricio Endo [UNESP] (My University, 2014)
Family agriculture, mostly represented by rural settlements especially in the state of São Paulo, makes up rural establishments in Brazil. Current investigation collects, analyzes and compares data on farmers on two rural settlements in the western region of the state of São Paulo, specifically in the municipality of Rancharia, with regard to their socioeconomic, financial and productive infrastructure profile, coupled to information on eventual restrictions to rural credit, by an analysis based on descriptive statistics. Results show that there are different factors between farmers and production systems, which cause loan restrictions due to such differences as age, agricultural and cattle-breeding activity, technical assistance and management. The valorization of these differences should be taken into account for the construction of new events, without extremes, and work for situations featuring demand-based development and characteristics of the locality
Keywords: Family agriculture; Rural credit; Descriptive statistics; Regional development